Digital Transformation in Human Resource Management: A Study of Organizations in Mataram City - Muhamad Ahyat; Nizar Hamdi; Zaulkarnaen; Indah Ariffianti (Journal of Management, 2026)
This study aims to analyze the implementation of digital transformation in Human Resource Management (HRM) within organizations in Mataram City, Indonesia. The research employs a qualitative approach with a case study design to gain an in-depth understanding of how digital technologies are integrated into HR practices, as well as the benefits and challenges associated with their implementation. Data were collected through in-depth interviews, observations, and documentation studies involving HR managers, staff, and employees who are directly engaged in digital HRM processes.The findings indicate that digital transformation has significantly improved the efficiency, transparency, and effectiveness of HR functions, particularly in areas such as recruitment, performance management, and employee development. The use of digital systems such as HRIS, e-recruitment platforms, and e-learning tools has enabled organizations to streamline processes, support data-driven decision-making, and enhance employee competencies. However, the study also reveals several challenges, including limited digital literacy, resistance to change, infrastructure constraints, and data security concerns, which hinder the optimal implementation of digital HRM.The study concludes that while digital transformation in HRM has a positive impact on organizational performance, its success depends on the integration of technology, human resources, and organizational culture. Strong leadership commitment and continuous capacity building are essential to ensure sustainable digital transformation. This research contributes to the development of HRM literature by providing empirical insights from a local context and offers practical recommendations for organizations seeking to implement digital HR practices effectively.